Translational regulation shapes the molecular landscape of complex disease phenotypes - Schafer, Sebastian; Adami, Eleonora; Heinig, Matthias; Rodrigues, Katharina E Costa; Kreuchwig, Franziska; Silhavy, Jan; van Heesch, Sebastiaan; Simaite, Deimante; Rajewsky, Nikolaus; Cuppen, Edwin; Pravenec, Michal; Vingron, Martin; et al. (Nature communications, 2015)
The extent of translational control of gene expression in mammalian tissues remains largely unknown. Here we perform genome-wide RNA sequencing and ribosome profiling in heart and liver tissues to investigate strain-specific translational regulation in the spontaneously hypertensive rat (SHR/Ola). For the most part, transcriptional variation is equally apparent at the translational level and there is limited evidence of translational buffering. Remarkably, we observe hundreds of strain-specific differences in translation, almost doubling the number of differentially expressed genes. The integration of genetic, transcriptional and translational data sets reveals distinct signatures in 3'UTR variation, RNA-binding protein motifs and miRNA expression associated with translational regulation of gene expression. We show that a large number of genes associated with heart and liver traits in human genome-wide association studies are primarily translationally regulated. Capturing interindividual differences in the translated genome will lead to new insights into the genes and regulatory pathways underlying disease phenotypes.
Keywords: Liver; játra; sekvenční analýza RNA; ribozomy; Hypertension; Gene Expression Regulation; mužské pohlaví; potkani inbrední SHR; fenotyp; regulace genové exprese; Sequence Analysis, RNA; Phenotype; Proteome; myokard; zvířata; Rats, Inbred BN; potkani inbrední BN; Myocardium; hypertenze; proteom; Rats, Inbred SHR; Ribosomes; Male; Animals